2,5-dioxido-1,4-benzoquinonediimine (H2L2-), a hydrogen-bonding noninnocent bridging ligand related to aminated topaquinone: different oxidation state distributions in complexes [(bpy)(2)Ru(2)(mu-H2L)](n) (n=0,+,2+,3+,4+) and [(acac)(2)Ru(2)(mu-H2L)] - Kar, S.; Sarkar, B.; Ghumaan, Sandeep; Janardanan, D.; van Slageren, J.; Fiedler, Jan; Puranik, Vedavati G.; Sunoj, R. B.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry - a European Journal, 2005)
{The symmetrically dinuclear title compounds were isolated as diamagnetic [(bpy)(2)Ru(mu-H2L)Ru(bpy)(2)]- (ClO4)(2) (1-(ClO4)(2)) and as paramagnetic [(acac)(2)Ru(mu-H2L)Ru(acac)(2)] (2) complexes (bpy = 2,2'-bipyridine; acac(-) -
Keywords: bridging ligands; Density functional calculations; EPR spectroscopy; N; O ligands; ruthenium

Effect of 2-(2-pyridyl)azole-based ancillary ligands (L1-4) on the electrophilicity of the nitrosyl function in [Ru-II(trpy)(L1-4)(NO)](3+) [trpy=2,2 `: 6 `,2 `'-terpyridine]. synthesis, structures, and spectroscopic, electrochemical, and kinetic aspects - Chanda, N.; Paul, D.; Kar, S.; Mobin, Shaikh M.; Datta, Anindya; Puranik, Vedavati G.; Rao, K. K.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2005)
Ruthenium nitrosyl complexes [Ru(trpy)(L1-4)(NO)](3+) (13-16) [trpy = 2,2':6',2"-terpyridine, L-1 = 2-(2-pyridyl)-benzoxazole, L-2 = 2-(2-pyridyl)benzthiazole, L-3 = 2-(2-pyridyl)benzimidazole, L-4 = 1-methyl-2-(2-pyridyl)-1H-benzimidazole] were obtained in a stepwise manner starting from [Ru-II(trpy)(L1-4) (Cl)]ClO4 (1-4) &RARR; [Ru-II(trpy)(L1-4) (H2O)](ClO4)(2) (5-8) &RARR; [Ru-II(trpy)(L1-4) (NO2)ClO4 (9-12) &RARR; [Ru-II(trpy)(L-1,L-2,L-4) (NO)](ClO4)(3) (13, 14, 16)/[Ru-II(trpy)(L-3) (NO)](Cl)(4))(2)(NO3) (15). Crystal structures of 1, 2, 4, 9, 12, 13, 15, and 16 established the stereoretentive nature of the transformation processes. Though the complexes of L1, L3, and L 4 were isolated in the isomeric form A (π-acceptor trpy and azole ring in the equatorial plane and the pyridine and chloride donors in the axial positions), complexes of L 2 preferentially stabilized in form B (trpy and pyridine in the equatorial plane and the azole ring and chloride donors in the axial positions). The v(NO) stretching frequency varied in the range of 1957-1932 cm(-1), 13 &MGT; 14 &MGT; 15 > 16, primarily depending on the electronic aspects of L as well as the isomeric structural forms. The coordinated nitrosyl function underwent successive reductions of [Ru-II-NO+](3+) &RARR; [Ru-II-NO&BULL;](2+) and [Ru-II-NO&BULL;](2+) - [Ru-II-NO-](+), and the first reduction potential follows the order 14 > 13 &MGT; 15 &AP; 16. The nearly axial EPR spectra having nitrogen hyperfine splittings (A &AP; 26 G) at 77 K of 13(-)-16(-) with (g) &AP; 2.0 established that the reduction process is largely centered around the nitrosyl function. Despite an appreciably high v(NO), the complexes were found to be unusually stable even in the aqueous medium. They transformed slowly and only partially into the corresponding nitro derivatives in H2O (k &AP; 10(-4) s(-1) and K = 0.4-3.8). The chloro (1-4), aqua (5-8), and nitro (9-12) derivatives displayed reasonably strong emissions near 700 nm at 77 K (φ = 10(-1)-10(-2)). The aqua derivative 7 was found to interact with the calf thymus and the circular form of p-Bluescript SK DNA.

Unusual monodentate binding mode of 2,2 `-dipyridylamine (L) in isomeric trans(acac)(2)Ru-II(L)2, trans-[(acac)(2)Ru-III(L)(2)]ClO4, and cis-(acac)(2)Ru-II(L)(2) (acac = acetylacetonate). Synthesis, structures, and spectroscopic, electrochemical, and magn - Kar, S.; Chanda, N.; Mobin, Shaikh M.; Urbanos, F. A.; Niemeyer, M.; Puranik, Vedavati G.; Jimenez-Aparicio, Reyes; Lahiri, Goutam Kumar (Inorganic Chemistry, 2005)
{The reaction of cis-Ru(acac)(2)(CH3CN)(2) (acac = acetylacetonate) with 2,2'-dipyridylamine (L) in ethanolic medium resulted in facile one-pot synthesis of stable [(acac)(2)Ru-III(L)]ClO4 ([1]ClO4), trans-[(acac)(2)Ru-II(L)2] (2), trans[(acac)(2)Ru-III(L)(2)[ClO4 ([2]ClO4), and cis-[(acac)(2)Ru-II(L)(2)] (3). The bivalent congener 1 was generated via electrochemical reduction Of [1]ClO4. Although in [1](+) the dipyridylamine ligand (L) is bonded to the metal ion in usual bidentate fashion, in 2/[2](+) and 3, the unusual monodentate binding mode of L has been preferentially stabilized. Moreover, in 2/[2](+) and 3, two such monodentate L's have been oriented in the trans- and cis-configurations, respectively. The binding mode of L and the isomeric geometries of the complexes were established by their single-crystal X-ray structures. The redox stability of the Ru(II) state follows the order 1 < 2 much less than 3. In contrast to the magnetic moment obtained for [1]ClO4

2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz)-derived [Ru-II(tptz)(acac)(CH3CN)](+) and mixed-valent [(acac)(2)Ru-III(mu-tptz-H+)(-)Ru-II(acac)(CH3CN)](+) - Ghumaan, Sandeep; Kar, S.; Mobin, Shaikh M.; Harish, B.; Puranik, Vedavati G.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
Mononuclear [Ru-II(tptz)(acac:)(CH3CN)]ClO4 ((ClO4)-Cl-[1]) and mixed-valent dinuclear [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(CH3CN)]ClO4 ([5]ClO4; acac = acetylacetonate) complexes have been synthesized via the reactions of Ru-II(acac)2(CH3CN)(2) and 2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz), in 1:1 and 2:1 molar ratios, respectively. In [1]ClO4, tptz binds with the Ru-II ion in a tridentate N,N,N mode (motif A), whereas in [5]ClO4, tptz: bridges the metal ions unsymmetrically via the tridentate neutral N,N,N mode with the Ru-II center and cyclometalated N,C- state with the Ru-III site (motif F). The activation of the coordinated nitrile function in [1]ClO4 and [5]ClO4 in the presence of ethanol and alkylamine leads to the formation of iminoester ([2]ClO4 and [7]ClO4) and amidine ([4]ClO4) derivatives, respectively. Crystal structure analysis of [2]ClO4 reveals the formation of a beautiful eight-membered water cluster having a chair conformation. The cluster is H-bonded to the pendant pyridyl ring N of tptz and also with the O atom of the perchlorate ion, which, in turn, makes short (C-H––-O) contacts with the neighboring molecule, leading to a H-bonding network. The redox potentials corresponding to the (RuI)-I-I state in both the mononuclear {[(acac)(tptz)Ru-II-N=-C-CH3]ClO4 ([1]ClO4) >> [(acac)(tptz)Ru-II-NH=C(CH3)-OC2H5]ClO4 ([2]ClO4) > [(acac)(tptz)(RuNH2)-N-II-C6H4(CH3)]ClO4 ([3]ClO4) > [(acac)(tptz)Ru-II-NH=C(CH3)-NHC2H5]ClO4 ([4]ClO4)} and dinuclear {[(acac)(2)Ru-III-{mu-tptz-H+)(-)}Ru-II(acac)(N equivalent to C-CH3)]ClO4 {(mu-tptz-H+)(-)}Ru-II(acac)(N equivalent to C-CH3)]ClO4 ([5]ClO4), [(acac)(2)Ru-III[(mu-tptz-H+(N-O ([6]ClO4), [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(NH=C(CH3)-OC2H5)]ClO4( [7]ClO4), and [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(NC4H4N)]ClO4 ([8]ClO4), complexes vary systematically depending on the electronic nature of the coordinated sixth ligands. However, potentials involving the Ru-III center in the dinuclear complexes remain more or less invariant. The mixed-valent (RuRuIII)-Ru-II species ([5]ClO4-[8]ClO4) exhibits high comproportionation constant (K-c) values of 1.1 X 10(12)-2 x 109, with substantial contribution from the donor center asymmetry at the two metal sites. Complexes display Ru-II- and Ru-III-based metal-to-ligand and ligand-to-metal charge-transfer transitions, respectively, in the visible region and ligand-based transitions in the UV region. In spite of reasonably high K, values for [5]ClO4[8]ClO4, the expected intervalence charge-transfer transitions did not resolve in the tpical near-IR region up to 2000 nm. The paramagnetic (RuRuIII)-Ru-II species ([5]ClO4-[8]ClO4) displays rhombic electron paramagnetic resonance (EPR) spectra at 77 K (< g > similar to 2.15 and Delta g similar to 0.5), typical of a low-spin Ru-III ion in a distorted octahedral environment. The one-electron-reduced tptz complexes [RuII(tptz center dot-)(acac)(CH3CN)] (1) and [(acac)(2)Ru-III{mu-tptz-H+)(center dot 2-)}-Ru-II(acac)(CH3CN)] (5), however, show a free-radical-type EPR signal near g = 2.0 with partial metal contribution.

Dynamic modeling of hydro- formylation of 1-decene on Rh/C catalyst in bubble colunm slurry reactor - Upkare, Makarand M.; Rajurkar, Kalpendra B.; Das, Samir K.; Jaganathan, Rengaswamy (International Conference on Modeling, Optimization, and Computing, 2010)
A dynamic model has been developed for the bubble column slurry reactor operating under non-isothermal conditions. The model consists of mass and heat balance equations for the gas and liquid phases and the catalyst particle. The model equations consisted of partial differential equations (PDE) which were converted to ordinary differential equations (ODE) by using finite difference relationships for the spatial derivatives and the ordinary differential equations for the time derivatives (Numerical Method of Lines-NMoL). The model was applied to describe the dynamic behaviour of bubble column slurry reactor during the hydroformylation of 1-decene on Rh/C catalyst. Model simulations were performed to obtain a meaningful path to steady state and to reproduce the other characteristics of the dynamic behaviour of the reactor. Under given conditions, the reaction required approximately 3750 seconds to reach the steady state concentrations at various reactor positions. It was observed with increase in the fluid velocities, the dynamics of the system was altered to 2500 seconds to reach the steady state condition. The effect of axial dispersion on the substrate concentration and the temperature rise along the reactor was further studied and discussed.
International Conference on Modeling, Optimization, and Computing, Durgapur, INDIA, OCT 28-30, 2010
Keywords: axial dispersion; bubble column slurry reactor; Dynamic modeling; method of line; PDE solutions

Mathematical modeling and simulation of bubble column reactor for aerial liquid phase cyclohexane oxidation - Upkare, Makarand M.; Rajurkar, Kalpendra B.; Gupta, Pankaj R.; Jaganathan, Rengaswamy (International Conference on Modeling, Optimization, and Computing, 2010)
Cyclohexane oxidation is an important but complex commercial reaction, wherein the desired product, K-A oil appears as an intermediates of the reaction sequence. A mathematical model has been developed for the bubble column reactor operating under isothermal conditions. The mass and energy model equations consisted of stiff ODEs. The model was applied to describe the behavior of bubble column reactor for aerial liquid phase cyclohexane oxidation. Effect of initial substrate concentration, catalyst loading and temperature was studied and discussed in detail. Conclusions were presented at the end of the study.
International Conference on Modeling, Optimization, and Computing, Durgapur, INDIA, OCT 28-30, 2010
Keywords: K-A Oil Selectivity; Mathematical modeling; substrate conversion and product yield analysis